Proses Adaptasi Penyandang Disabilitas dengan Masyarakat di Perumahan Inklusi Kabupaten Trenggalek - Lahitani, Kirana Andini Janna; Prasetyo, Franciscus Adi; Mayangsari, Wahyuni Mayangsari (Jurnal Intervensi Sosial dan Pembangunan, 2025)
People with disabilities in society experience many problems in the form of stigma, discrimination, segregation, and so on, leading to exclusive society conditions. However, when referring to the development of the last two decades, there has been a shift from an exclusive to an inclusive society. In line with these developments, currently in Prambon Village, Tugu District, Trenggalek Regency there is an inclusive residential area initiated by the Naeema Foundation. People with disabilities in inclusive residential have close ties with the community, such as being involved in mutual cooperation activities, community service, and religious activities. This research focuses on the process of adapting persons with disabilities to the community and aims to find out and analyze in depth about the adaptation process. This research uses a qualitative approach with a case study type. The results of this study show that people with disabilities living in inclusive residential are able to adapt to the community. Persons with disabilities living in inclusive housing are able to go through several stages of the adaptation process starting from the indecision conditions of adapting, the process of determining adaptation strategies, and finally being able to adapt with society. This research concludes that inclusive housing is able to act as a mediator in creating an inclusive society that is friendly, caring and helpful to each other between people with disabilities and the general public.Keywords: People with Disabilities, Adaptation Process, Inclusive Residential.